FINANCIAL VALUE OF MOSSURIZE FOREST IN MOZAMBIQUE - Júlio, Félita Joaquim; Falcão, Mário Paulo; Júnior, Romano Timofeiczyk; Buratto, David Alexandre; Hersen, Amarildo (Floresta, 2019)
The Mossurize forest does not yet have a financial value and therefore there is a need to estimate and quantify it, as this procedure will provide the financial reference of the same, thus stimulating alternative sources of income for rural communities and concern with the use of sustainable. practices in the use of forest resources. The objective of this work was to calculate the financial value of the Mossurize forest, Manica province, Republic of Mozambique, with the identification of the value of forest products and thus provide economic subsidy for the rational exploitation of their resources. This work was developed in an area of 41,331 hectares. To characterize the vegetation cover was used the inventory data of the tree species. The calculation methodology, by sampling, made use of quantification procedures for the commercial value species, Annual Acceptable Cut (AAC), Unit and Annual Cost, Total Revenue, Net Benefit (NB) and Net Present Value (NPV). The results indicate a positive financial value for this forest process, considering the commercial value of the species. It is highlighted the need to create and improve a sustainable forest management program and market stimulus for sustainable management products.